2012
DOI: 10.4028/www.scientific.net/amm.200.347
|View full text |Cite
|
Sign up to set email alerts
|

Study on Anti-Fog Films of Polyethylene Modified with Inorganic Micrometer Diatomite

Abstract: Abstract. Anti-fog films of low density polyethylene (LDPE) modified with micrometer diatomite were prepared by a process of blow molding. Through examination of antifogging property of the film added the anti-fog agents, the modification effectiveness of inorganic micrometer diatomite and the influence of different treating agents were studied with Fourier transform infrared spectrometer (FTIR), mechanical properties, and antifogging performances. The results indicate that the anti-fog property of the film ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…10 shows the variation of Young's modulus with diatomite weight fraction (Φf). It can be seen that the value of the modulus of elasticity increases non-linearly with the increasing weight fraction of the modified filler [29]. According to Hu et al [30], the slipping of macromolecular chains of the matrix is blocked by the inorganic filler particles.…”
Section: Correlation Between Tensile Strength and Diatomite Contentmentioning
confidence: 97%
“…10 shows the variation of Young's modulus with diatomite weight fraction (Φf). It can be seen that the value of the modulus of elasticity increases non-linearly with the increasing weight fraction of the modified filler [29]. According to Hu et al [30], the slipping of macromolecular chains of the matrix is blocked by the inorganic filler particles.…”
Section: Correlation Between Tensile Strength and Diatomite Contentmentioning
confidence: 97%
“…In addition, some scholars have found that diatomite has the effect of delaying the precipitation of the dripping agent. He et al 23 prepared microdiatomite-modified LDPE antifog film by blow molding method and studied the antifog performance and mechanical properties of the film. The results show that the film modified by inorganic micron diatomite with surface treatment agent has a more obvious antifog effect than that modified by antifog agent alone.…”
Section: Introductionmentioning
confidence: 99%